1985
DOI: 10.3189/s0022143000006638
|View full text |Cite
|
Sign up to set email alerts
|

Medial Moraines of the Haut Glacier D’arolla, Valais, Switzerland: Debris Supply and Implications For Moraine Formation

Abstract: ABSTRACT. The Haut Glacier d' Arolla displays three medial moraines: an ablation-dominant moraine east of the glacier centre line, an ice-stream interaction moraine west of the glacier centre line, and a medial-lateral supraglacial moraine complex along the western margin of the glacier. The eastern moraine is formed by the emergence of coarse angular clasts from a series of short longitudinal debris bands 1 km from the glacier terminus; this debris is derived from rock falls at the glacier head-wall, and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 11 publications
4
33
0
Order By: Relevance
“…Previous authors (Small and others, 1979;Gomez and Small, 1985;Small, 1987) suggested that the eastern medial moraine is formed by the emergence of coarse angular clasts from a series of short longitudinal debris bands, identical to the debris emerging along planes of primary stratification described here. Introducing the concept of folding of rockfall-bearing primary stratification into the hypothesis of medial moraine formation explains the intermittent nature of the moraine lenses and the V-shape of some moraines (noted in Fig.…”
Section: Medial Moraine Formationsupporting
confidence: 70%
See 3 more Smart Citations
“…Previous authors (Small and others, 1979;Gomez and Small, 1985;Small, 1987) suggested that the eastern medial moraine is formed by the emergence of coarse angular clasts from a series of short longitudinal debris bands, identical to the debris emerging along planes of primary stratification described here. Introducing the concept of folding of rockfall-bearing primary stratification into the hypothesis of medial moraine formation explains the intermittent nature of the moraine lenses and the V-shape of some moraines (noted in Fig.…”
Section: Medial Moraine Formationsupporting
confidence: 70%
“…Mair and others, 2001), and the development of high-resolution glacier flow modelling (Hubbard and others, 1998;Hubbard and Hubbard, 2000). The formation of medial moraines and sediment transport pathways have also been described at the glacier (Small and others, 1979;Gomez and Small, 1985;Small, 1987).…”
Section: Field Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Haut Glacier d'Arolla is a north-flowing valley glacier at the southern end of the Arolla valley, which forms the western branch of There is a substantial literature on many aspects of Haut Glacier d'Arolla, for example sediment transfer (e.g., Gomez and Small, 1985;Small, 1987), glacial melt-water chemistry (e.g., Brown et al, 1994), glacier geometry (Sharp et al, 1993), subglacial hydrology (e.g., Hubbard et al, 1995;Nienow et al, 1998), interactions between glacier hydrology and dynamics (e.g., Mair et al, 2001), and highresolution glacier flow modeling Hubbard and Hubbard, 2000).…”
Section: Study Areamentioning
confidence: 99%